2007
DOI: 10.1037/0012-1649.43.4.918
|View full text |Cite
|
Sign up to set email alerts
|

The role of child adrenocortical functioning in pathways between interparental conflict and child maladjustment.

Abstract: This study examined the interplay between interparental conflict and child cortisol reactivity to interparental conflict in predicting child maladjustment in a sample of 178 families and their kindergarten children. Consistent with the allostatic load hypothesis (McEwen & Stellar, 1993), results indicated that interparental conflict was indirectly related to child maladjustment through its association with individual differences in child cortisol reactivity. Analyses indicated that the multimethod assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(168 citation statements)
references
References 80 publications
5
160
2
1
Order By: Relevance
“…The number of interactions tested may be a limitation of the current design, but allowed us to examine differ ent characteristics of the marital and parent-child relationships separately to better understand nuances of the way that family relationships are related to patterns of stress responding. However, it was unexpected that neither marital conflict nor parent-child relationship quality (nor interactions between them) were related to cortisol, given that the TSST did predict significant cortisol reactivity, and past research has demonstrated links between fam ily relationships and cortisol reactivity, including reactivity to the same stressor utilized in this study (Davies et al, 2007;LucasThompson, 2012). It is possible that, particularly in this age range, family relationships may be related to more dynamic estimates of acute cortisol reactivity, or may instead be related to other dimen sions of cortisol functioning (e.g., patterns of diurnal cortisol production, which have also been linked in past research with family functioning (Lucas-Thompson & Hostinar, 2013;Pendry & Adam, 2007).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The number of interactions tested may be a limitation of the current design, but allowed us to examine differ ent characteristics of the marital and parent-child relationships separately to better understand nuances of the way that family relationships are related to patterns of stress responding. However, it was unexpected that neither marital conflict nor parent-child relationship quality (nor interactions between them) were related to cortisol, given that the TSST did predict significant cortisol reactivity, and past research has demonstrated links between fam ily relationships and cortisol reactivity, including reactivity to the same stressor utilized in this study (Davies et al, 2007;LucasThompson, 2012). It is possible that, particularly in this age range, family relationships may be related to more dynamic estimates of acute cortisol reactivity, or may instead be related to other dimen sions of cortisol functioning (e.g., patterns of diurnal cortisol production, which have also been linked in past research with family functioning (Lucas-Thompson & Hostinar, 2013;Pendry & Adam, 2007).…”
Section: Discussionmentioning
confidence: 81%
“…In line with past research (Davies et al, 2007;Lucas-Thompson, 2012), we hypothesized that marital conflict would predict hyporeactive cortisol responses. Although there are contrasting findings about whether family conflict predicts hypo-or hyperreactive cardiovascular responses (e.g., El-Sheikh, 1994;Lucas-Thompson, 2012), there is more empirical support for the hyperreactivity hypothesis.…”
Section: The Current Studymentioning
confidence: 81%
“…Further emphasizing the far-reaching consequences of inter-adult conflict is the body of work that shows the repercussions on children's physiology (Davies et al 2007). showed that children's fear responses to inter-parental conflict were predictors of their elevated cortisol reactivity to conflict, especially for children exhibiting involvement in conflicts.…”
Section: Family Conflict Is Related To Child and Family Dysfunctionmentioning
confidence: 99%
“…44,[48][49][50]56,58,59,62 Intervention duration ranged from ,1 month (n = 1) 53 to .1 year (n = 6), 44,47,[54][55][56]58,61 and it was most common for studies to assess outcomes within #6 months after the intervention began (n = 8) [48][49][50]53,57,59,62 or .1 year after intervention initiation (n = 8). 28,33,39,41,43,44,46,55 Fifteen studies included intervention components that involved both parents and children, and 2 studies tested interventions that involved only children. 53,60 All studies assessed cortisol by using saliva samples.…”
Section: Figurementioning
confidence: 99%
“…[16][17][18] Dysregulation can entail both hyper-and hypoactivity, which may be reflected by atypical diurnal secretion and enhanced or reduced responsiveness to stress. 13,14,16,[19][20][21] Children exposed to adversity exhibit lower morning cortisol values, 22 blunted cortisol awakening response, 23 shallow morning to evening slope, 21,[24][25][26] greater area under the daytime cortisol curve, 24,27 and both blunted [28][29][30] and elevated 31,32 cortisol response to acute stressors relative to unexposed children. Dysregulated cortisol secretion has been associated with numerous chronic health problems, including metabolic syndrome, 33 coronary artery disease, 34 psychiatric disorders, [35][36][37] and others.…”
mentioning
confidence: 99%